¿Existe un lugar para el arbitraje dentro del sistema de reparaciones practicado por la Corte Interamericana de Derechos Humanos? - Ríos Carrillo, Piero (2020)
This work addresses the role which arbitration could occupy within the reparations system developed by the Inter-American Court of Human Rights when solving contentious disputes. In that sense, the only two precedents in which the Court entertained the possibility of considering arbitration as an alternative means for the determination of reparations shall be described: Garrido and Baigorria vs. Argentina and Chaparro Alvarez and Lapo Iñiguez vs. Ecuador. From the analysis of these two precedents, the author will try to: a) Identify and characterize the different approaches taken by the Court in each case; b) evaluate whether these two approaches are consistent with the relevant international human rights law and the general principles of arbitration; c) point out how and when arbitration can be used as an alternative mechanism to determine the reparations in a case concerning human rights violations.human rights violations.